Cu-Based Multicomponent Metallic Compound Materials as Electrocatalyst for Water Splitting - Wang, Peijia; An, Jingjing; Ye, Zhenyu; Cai, Wei; Zheng, Xiaohang (Frontiers in Chemistry, 2022)
In this study, Cu-based multicomponent metallic compound materials M-Cu (M = Mn, Fe, Co, Ni, and Pt) were studied as electrocatalytic materials for water splitting. Different metal materials attached to the copper foam substrate can change the valence states of copper and oxygen, resulting in the change of electronic structure of the materials, thus changing its catalytic activity.